FAQ (Frequently Asked Questions) ChatBot for Conversation - Sethi, Farhana (International Journal of Computer Sciences and Engineering, 2020)
ChatBot is a software application used to conduct an on-line chat conversation via text or text-to-speech, in instead of providing direct contact with a live human. However, An FAQ (Frequently Asked Questions) chatBot is a type of internet bot or software application that is beneficial for answering some of the most frequently asked questions your customers may have. FAQ bots help direct customers to the right website pages and provide answers easily any time of the day. In this paper, we present the architecture and prototype of a FAQ chatBot.